Can Global De-Carbonization Inhibit Developing Country Industrialization? - Mattoo, Aaditya; Subramanian, Arvind; van der Mensbrugghe, Dominique; He, Jianwu (Oxford University Press on behalf of the World Bank, 2013)
Most economic analyses of climate change have focused on the aggregate impact on countries of mitigation actions. We depart first in disaggregating the impact by sector, focusing particularly on manufacturing output and exports. Second, we decompose the impact of a modest agreement on emissions reductions—17 percent relative to 2005 levels by 2020 for industrial countries and 17 percent relative to business-as-usual for developing countries—into three components: the change in the price of carbon due to each country's emission cuts per se; the further change in this price due to emissions tradability; and the changes due to any international transfers (private and public). Manufacturing output and exports in low carbon intensity countries such as Brazil are less affected. In contrast, in high carbon intensity countries, such as China and India, even a modest agreement depresses manufacturing output by 3–3.5 percent and manufacturing exports by 5.5–7 percent. The increase in the carbon price induced by emissions tradability hurts manufacturing output most while the real exchange rate effects of transfers hurt exports most.